2021
DOI: 10.3390/molecules26216485
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Geometries and Catalytic Applications of CeO2 from a DFT Outlook

Abstract: Rare earth metal oxides (REMOs) have gained considerable attention in recent years owing to their distinctive properties and potential applications in electronic devices and catalysts. Particularly, cerium dioxide (CeO2), also known as ceria, has emerged as an interesting material in a wide variety of industrial, technological, and medical applications. Ceria can be synthesized with various morphologies, including rods, cubes, wires, tubes, and spheres. This comprehensive review offers valuable perceptions int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 197 publications
0
8
0
Order By: Relevance
“…Ceria is used in a broad array of applications such as catalysts [1,2], photocatalysts, optoelectronics and opto-magnetic devices [3,4]. One of the features that renders ceria useful for catalysis is its ability to release or uptake oxygen from its lattice without substantial structural re-arrangement or the loss of its fluorite lattice [5,6]. In the fluorite structure, Ce atoms demonstrate a change in oxidation state from Ce 4+ to Ce 3+ and increase the tendency for redox [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ceria is used in a broad array of applications such as catalysts [1,2], photocatalysts, optoelectronics and opto-magnetic devices [3,4]. One of the features that renders ceria useful for catalysis is its ability to release or uptake oxygen from its lattice without substantial structural re-arrangement or the loss of its fluorite lattice [5,6]. In the fluorite structure, Ce atoms demonstrate a change in oxidation state from Ce 4+ to Ce 3+ and increase the tendency for redox [7].…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2 ‐based catalysts undergo thermal ageing; this reduces OSC as a result of sintering of the oxide particles during heating. Nevertheless, pure CeO 2 is widely used both as a catalyst support 23 and a catalyst itself 24,25 . The most effective thermal stabilizer of CeO 2 is ZrO 2 , particularly when solid solutions with the Ce x Zr 1‐ x O 2 composition are formed 21,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, pure CeO 2 is widely used both as a catalyst support 23 and a catalyst itself. 24,25 The most effective thermal stabilizer of CeO 2 is ZrO 2 , particularly when solid solutions with the Ce x Zr 1-x O 2 composition are formed. 21,26,27 However, although the specific surface areas of such systems can reach 200 m 2 g −1 , 26 they are usually significantly lower.…”
Section: Introductionmentioning
confidence: 99%
“…12 Previous experiments have demonstrated that ceria doping can efficiently improve its reducibility and catalytic redox activity. 13,14 Metiu et al used density functional theory (DFT) calculations to evidence that doping can dramatically weaken the binding of the ceria surface oxygen to the rest of the lattice and make ceria accelerate the O* migration 15 and Lawrence et al also suggested the oxygen vacancy formation energy is an important probe of the reducibility of the oxide. 16 In addition, Ir/CeO 2 presents a highly active and selective catalyst for hydrogen production by the oxidative steam-reforming of ethanol, the promotion effect is partly assigned to its enhanced reducibility and oxygen storagerelease capacity.…”
Section: Introductionmentioning
confidence: 99%